2014
DOI: 10.1097/hcm.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Intensive Care Unit Length of Stay

Abstract: Bed rest or immobilization is frequently part of treatment for patients in the intensive care unit (ICU) with critical illness. The average ICU length of stay (LOS) is 3.3 days, and for every day spent in an ICU bed, the average patient spends an additional 1.5 days in a non-ICU bed. The purpose of this research study was to analyze the effects of early mobilization for patients in the ICU to determine if it has an impact on the LOS, cost of care, and medical complications. The methodology for this study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 26 publications
1
41
1
3
Order By: Relevance
“…Mechanical ventilation is one of the most common interventions implemented in intensive care units (ICU) or critical care units. The length of stay in ICU varies between 24 hr to 132 days (Arabi, Venkatesh, Haddad, Al Shimemeri, & Al Malik, ), with an average length of stay of about 3.3 days (Hunter, Johnson, & Coustasse, ). The average daily cost of stay in ICU represents one third of total health care cost, and is steadily increasing (Shorr, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation is one of the most common interventions implemented in intensive care units (ICU) or critical care units. The length of stay in ICU varies between 24 hr to 132 days (Arabi, Venkatesh, Haddad, Al Shimemeri, & Al Malik, ), with an average length of stay of about 3.3 days (Hunter, Johnson, & Coustasse, ). The average daily cost of stay in ICU represents one third of total health care cost, and is steadily increasing (Shorr, ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the disabilities of patients, the most important issue for ICH patients is care after the disease has been stabilized. Research has shown that early mobilization will decrease the LOS in ICU [49]. Proactive palliative care consultations for high-risk patients, for example, ICH patients, will significantly decrease the LOS in ICU [50].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the implementation of an intensive PT program may not be indicated for all critically ill patients who require mechanical ventilation for at least 4 days. Much of the rationale for providing intensive PT has been based on shortening ICU and hospital lengths of stay, and therefore on reducing hospital costs (53). Though PT is a relatively safe intervention, it is labor intensive (54).…”
Section: Discussionmentioning
confidence: 99%